The Influence of Inquiry Learning Model Implementation on Students Critical Thinking Ability in Class Learning Activities - Mohzana Mohzana; Amaludin Bahansubu; Hasbi Taobah Ramdani; Muhammad Syahrul; Antonius Rino Vanchapo (Departement of Mathematics Education, 2023)
This study aims to optimize the pedagogic competence of teachers in Class X.E MAN 2 Payakumbuh Even Semester 2022/2023 Academic Year in compiling teaching modules through continuous academic supervision. The research method is school action research. The subjects of this study were teachers in Class X.E MAN 2 Payakumbuh Even Semester 2022/2023 Academic Year, a total of 20 people, 15 general subject teachers and 5 Islamic Religious Education subjects. This research was conducted in two cycles and at the end of each cycle an analysis of the teachers’ ability to make teaching modules and their application in class was carried out. Data collection techniques in this study used observation sheets, documentation and field notes on teachers’ development. The method used in data analysis was a quantitative descriptive analysis method. The results showed that the optimization of the pedagogic competence of teachers in Class X.E MAN 2 Payakumbuh Even Semester 2022/2023 Academic Year in compiling teaching modules through continuous academic supervision has increased. Based on the results of the research and discussion it can be concluded that through the application of continuous academic supervision it can improve the ability of teachers to make teaching modules at MAN 2 Payakumbuh. This can be seen from the increase in their average ability from cycle I to cycle II. The average increase per indicator for the assessment of the making of teaching modules was an increasing from 73.00 quite satisfactory category (C) in cycle I to 88.75 satisfactory category (B+) with an increasing percentage of 21.58%. While the average teachers’ ability to make teaching modules is in the satisfactory category. From 73.54 quite satisfactory (C) in cycle I increased to 90.63 satisfactory category (B+) with an increase percentage of 23.24%. Thus it can be concluded that optimizing pedagogical competencies can improve the ability of teachers in Class X.E MAN 2 Payakumbuh Even Semester 2022/2023 Academic Year in compiling teaching modules through continuous academic supervision